Six-Phase Voltage Source Inverter Efficiency Optimization Using Advanced Switching Techniques - Taylor, Joshua (My University, 2020)
Since the late 1990s, lots of attention has been given to the development of multi-phase motor drives due to the momentous interest in developing greener methods of transportation and the increased benefits when compared to their three-phase counterparts. These benefits include improved fault-tolerant control, reduced torque ripple, improved motor power density, and reduced DC-link capacitance which has resulted in an amplified interest in multi-phase machines for electric ship propulsion, electric aircraft, and traction electric motors (electric and hybrid road vehicles). When looking specifically into multi-phase machines that are made up of six-phases, different topologies have been researched that include altering the phase shift between the different windings or winding sets as well as the number of neutral points within the machine. Out of all possible combinations, there are three common six-phase machine topologies studied in the literature. First is the six-phase machine with a 60 degree phase shift between each of the machine windings – referred to as an asymmetrical six-phase machine. The second and third topologies are a six-phase machine with two sets of three-phase windings where one winding set has a phase shift from the other winding set (typically 30 degrees. When the two winding sets have a shared neutral point, the machine is referred to as an asymmetrical six-phase machine. Alternatively, when the two winding sets have isolated neutral points, the machine is referred to as a dual three-phase machine. From the recent surge in the literature regarding the added benefits of the dual three-phase machine compared to the other six-phase topologies, this thesis will mainly focus on the control and switching techniques specifically for the dual three-phase machine. With an in-depth analysis, the effect of different switching techniques will be observed on the overall efficiency of the six-phase voltage source inverter (VSI). Furthermore, using the Matlab/Simulink and PLECS environment with a dual three-phase drive system vector space decomposition (VSD) based model, an accurate drive model that incorporates the machine's dynamic behaviour and calculates the total losses of the VSI is also proposed. The VSI is connected to a 100 kW dual three-phase interior permanent magnet synchronous machine (IPMSM) and different switching techniques are applied to the inverter to properly control the six-phase drive system. Similar to their three-phase counterparts, dual three-phase machines can be controlled using sinusoidal carrier-based pulse width modulation (SPWM) and space vector pulse width modulation (SVPWM). This thesis explores the VSI efficiency when using different switching techniques proposed in the literature and proposes new techniques to improve the efficiency of the VSI. Additionally, a detailed plan for an experimental setup and testing procedure is provided for the switching techniques that are simulated throughout this thesis. This proposed testing procedure assumes a prototype six-phase VSI composed of six Infineon FF600R12IE4 IGBT modules that are connected to a dual three-phase 100 kW IPMSM. As the future work of this thesis includes experimental verification, the Matlab/Simulink drive model proposed in this thesis is designed with this particular setup in mind.